Medication-related burden from the perspective of the elderly - Alqallaf, Sayed Mahmood; Mattar, Layan; Ghuloom, Kawther; Alabbad, Kawther; Alshaikh, Fatema; Alhaddad, Mustafa (Medicine and Pharmacy Reports, 2022)
Living with extensive polypharmacy among the elderly population affects their quality of lives and medication compliance. The UK-developed (LMQ-3) which is a valid instrument designed to quantify medicine burden. The objectives of this study were to quantify medicines burden among community-dwelling elderly, describe the numbers and types of drugs used, and identify the risk factors that might need to be addressed. The descriptive cross-sectional study is designed to interview 500 Bahraini over 65 years of age using LMQ-3 questionnaire. Sample size was determined by Sloven’s formula. Data on socio-demographic characteristics and medication consumption patterns were collected then LMQ-3 and domains scores were compared by patient characteristics using descriptive statistics and statistical tests. Results found a wide range of burden among participants in Bahrain; ranging from moderate burden in almost a third of participants to high burden over two- thirds of participants. Burden was mainly driven by concerns about medicines, interferences of medicines with daily life and side effects. Higher LMQ-3 scores were associated with those who were employed, technical, aged ≥75 years, using ≥9 medicines, or using medicines four times a day. Anti-diabetics were the most prescribed medicines for the elderly. In conclusion, over two- thirds of participants experienced high burden. Being employed, technical, aged ≥75 years, using ≥9 medicines, or using medicines 4 times a day had the highest burden. These groups should become the main target for practitioners and pharmacists. Future studies should document potential herb-drug interactions among the elderly.